Germanium substrate loss during thermal processing - Kaiser, R. J.; Koffel, S.; Pichler, Peter; Bauer, A. J.; Amon, B.; Frey, Lothar; Ryssel, Heiner (Microelectronic Engineering, 2011)
Germanium layers are very attractive for future semiconductor devices due to their high carrier mobility. To form pn-junctions in such devices, ion implantation followed by an annealing step is the most feasible way. Several previous studies reported severe surface degradation during annealing of germanium without a capping layer. The observed deteriorations are, e.g., heavy surface roughness or even loss of bulk material. To study the loss of germanium, samples with patterned silicon dioxide layer were annealed at temperatures between 500 and 600 °C in different atmospheres. The chosen atmospheres were selected to be nominally inert (N2, Ar, or vacuum). Yet, the samples showed rates of substrate loss, e.g., up to 3 nm/min at 600 °C in Ar atmosphere. The resulting rates of substrate loss can be approximately described by Arrhenius laws with an activation energy of 2.08 + 0.21 eV in the case of Ar. Direct evaporation of germanium or germanium dioxide can be excluded because of the low vapor pressures reported in the literature. As mechanism, we propose the evaporation of germanium monoxide formed with residual oxidants such as oxygen or water vapor in the atmosphere used for processing. Rough calculations exhibit that a desorption rate of about 10-8 mol GeO per min is required in our experiments to achieve the maximum rate of substrate loss in argon at 600 °C. Results for the different atmospheres will be compared.
Keywords: Annealing; Doping profiles; Elemental semiconductors; Germanium; Thermal etching